Commentary: what difference does space make for interaction and interaction for space? - Stukenbrock, Anja (Space in language and linguistics, 2013)
Das Kapitel Commentary: What difference does space make for interaction and interaction for space? erschien in Space in Language and Linguistics auf Seite 401.